Cerium-based metal-organic framework having inherent oxidase-like activity applicable for colorimetric sensing of biothiols and aerobic oxidation of thiols - Dalapati, Rana; Sakthivel, Balasubramanian; Ghosalya, Manoj K.; Dhakshinamoorthy, Amarajothi; Biswas, Shyam (Crystengcomm, 2017)
A cerium-basedmetal-organic framework (MOF; 1) with a UiO-66 (UiO: University of Oslo) framework topology was synthesized solvothermally by employing 3,4-dimethylthieno[2,3-b] thiophene-2,5-dicarboxylic acid as a ligand. The MOF was thoroughly characterized by X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction, infrared spectroscopy, and thermogravimetric and N-2 sorption analyses. The activated material (1') retained its structural integrity in water, acetic acid and 1 M HCl solution. XPS investigation reveals the presence of both Ce(III) and Ce(IV) ions in 1. Owing to the presence of mixed-valence cerium ions, 1' was able to oxidize the chromogenic peroxidase substrate 3,3', 5,5'-tetramethylbenzidine (TMB) or 2,2'azinobis.3- ethylbenzothizoline-6-sulfonic acid) (AzBTS) in the absence of an external oxidizing agent. Thus, it showed inherent oxidase-like catalytic properties. Inspired by the excellent oxidase-mimicking activity of 1', a protocol was developed for the rapid colorimetric sensing of biothiols in NaAc buffer (0.2 M, pH = 4). The sensing ability of 1' towards cysteine was also demonstrated in human blood plasma. Furthermore, the redox-active cerium ions enabled 1' to exhibit excellent heterogeneous catalytic performance in aerobic oxidation catalysis of thiol compounds. The material is reusable (both as a sensor and as a catalyst), lowcost and highly stable, which renders it a promising candidate for the monitoring of biothiols in immunoassays and medical diagnosis as well as for industrial oxidation catalysis.